Spontaneous rupture of the renal calyx secondary to dysfunctional voiding (Indian Journal of Case Reports, 2021)
Spontaneous pelvicalyceal/ureteral rupture due to abnormal bladder dynamics or urinary retention is rare with only a few cases reported. We report a case of spontaneous fornix rupture secondary to increased intravesical pressure caused by dysfunctional voiding in a young female with mental subnormality with paralytic ileus as a presenting symptom. The patient settled with double J stenting and catheterization. A literature review of the upper tract rupture due to bladder dysfunction/urinary retention is presented along with a discussion of management options and prevention.